Correlation between pain assessment scale and neurovascular compression distance to the root exit zone in trigeminal neuralgia analysis using 3D CISS MRI sequence (Medical Journal of Indonesia, 2019)
BACKGROUND Trigeminal neuralgia (TN) is primarily caused by neurovascular compression (NVC) at root exit zone (REZ) in cerebellopontine angle cistern. In some NVC cases, it was suspected that clinical symptoms may be correlated with the distance of trigeminal nerve root to vascular contact. Pain assessment scale (PAS) was the most common scale used to evaluate TN pain, therefore this study was conducted to analyze the correlation between PAS usingnumeric rating scale (NRS) and distance from the NVC to REZ location in patients with TN using 3D CISS MRI sequence. METHODS This cross-sectional study was conducted at the Department of Radiology, Faculty of Medicine, Universitas Indonesia, Cipto Mangunkusumo Hospital, Jakarta, using secondary data of 32 patients, collected from Picture Archiving and Communication System from January 2013 to January 2016. Statistical analysis was performed using SPSS, version 20.0. Spearman p-value of < 0.05 was considered significant. RESULTS A total of 32 patients met the inclusion criteria. The mean (SD) distances from the NVC to the REZ were 2.1 (2.1), 2.31 (2.25), and 3.22 (2.63) mm on the shortest, medial, and lateral sides, respectively. The correlation coefficients (r) between the PAS value and the NVC distance in relation to the trigeminal nerve REZ were -0.39 (p = 0.021), -0.57 (p < 0.01), and -0.57 (p = 0.294) on the shortest, lateral, and medial sides, respectively. CONCLUSIONS PAS using the NRS instrument exhibited an inverse correlation to NVC distance to the REZ of the trigeminal nerve. Shorter distance increased the PAS value.